BAIT BOOSTER UTILIZATION ON BOTTOM GILLNET IN PALABUHANRATU BAY WATERS - Zulkarnain; Mawardi, Wazir; Sri Wiyono, Eko; Firdaus, Muhammad Fakhri (Departemen PSP IPB, 2025)
The technological status of bottom gillnet fishing gear (rampus net) and its fishing operation methods have not changed much in its development and tend to be static. This problem also occurs among rampus net fishermen in Palabuhanratu Bay, where there is a decrease in catch productivity. The technological innovation needed for rampus net fishing gear is the use of bait boosters to attract and gather fish so that they are easy to catch. The research activities were carried out using an experimental fishing method with 20 trips as replications by comparing between treatment of rampus net with the control. The results showed that there was an increase in catches in treatment of rampus net compared to the control. The catch consisted of 61.2% demersal fish and 38.8% pelagic fish, dominated by largehead hairtail fish. The productivity of the treatment of rampus net had a value greater than the control, namely 0.85 kg/net-piece and 0.50 kg/net-piece, respectively. The production margin of the catch of the rampus net treatment compared to the control was 70.5%. Key words: bait booster, bottom gillnet, Palabuhanratu Bay